Comparison between mehod of one-factor-at-a-time (OFAT) & design of experiment (DOE) in screening of immunoglobulin production stimulatesing factors - Muhd Abd Mursyid, W. Mohd. Saberi (2010)
The medium of mouse-mouse hybridoma, 192 producing IgG against 17-OHP was supplemented with seven different inducing agents at different range namely lysozyme, lipopolysaccharides (LPS), potassium phosphate, aldolase, essential amino acid, non-essential amino acid and sodium butyrate. This study aims to compare the statistical design of experiments (DOE) and one-factor-at-a-time (OFAT) method in screening immunoglobulin production stimulating factors. The culture medium supplemented with the inducer agents were screened using OFAT method and Plakett- Burman design method to determine inducer agent that gave positive effect. The effect of inducer concentration towards the antibody production was studied using enzyme-linked immunosorbent assay (ELISA) technique. The optimal concentrations for all the inducing agent were failed to be found in OFAT method. The standard culture medium without addition of inducer yield 0.234μg/ml of MAb. The culture supplemented with the inducer agent that yields MAb close to the standard was non-essential amino acid. Plakett-Burman design gave 12 runs with only the high level (+) and the low level (-) of the inducer were used. Potassium phosphate, LPS and sodium butyrate was found to be the most influential variable using Plakett-Burman design. Plakett-Burman design however indicates that all the point was insignificant and the interaction between inducer was not described. Plakett-Burman under DOE method gave the best time-wise compared to OFAT method in screening monoclonal antibody stimulating factors.